Scientific and theoretical bases for designing a model for forming future lawyers’ civic-mindedness - Raisa Mikhailovna Chumicheva; Anton Alexandrovich Gabovich (Вестник Майкопского государственного технологического университета)
The relevance of the research is determined by the need to search for new scientific, theoretical, methodological, substantive and technological foundations for the training future lawyers, as the intellectual and political elite of the state, possessing a stable civic position and ready to form a civil society and protect the rights of Russian citizens. The problem of the research is to study the features of training future lawyers and to determine the scientific and theoretical platform for designing a model for the formation of civic position of future lawyers in the legal clinic of a university. The purpose of the research is scientific substantiation and design of a model for the formation of the civic position of future lawyers in the legal clinic of a university. The research methodology and methods: content analysis of scientific research; theoretical analysis of pedagogical dilemmas in the training of future lawyers; forecasts of pedagogical fronts for the development of conditions for the development of the civic position of future lawyers in the process of professional training; designing a model for the development of the civic position of future lawyers in the legal clinic of a university. The research results are: transformational processes in the world change civil society (social stratification, lack of protection of the rights of a separate part of society, etc.) and become challenges to modern education in the training of future lawyers; integration and an interdisciplinary approach in the training of future lawyers determine scientific-theoretical, methodological, substantive and technological approaches to the development of the civil position of a future lawyer; designing a model for the development of the civic position of future lawyers in the legal clinic of a university makes it possible to make forecasts for the required competencies of this category of specialists, optimize the environment of a university - a legal clinic as a place of professional self-realization and manifestation of the civic position of a future lawyer. Key findings are: global trends are challenges for modern legal education; the training of future lawyers should be coupled with the formation of a civic position, understood as a willingness to serve their Fatherland, the state and its citizens; the design of innovative models for the training of future lawyers is focused on the integration of the processes of professional formation and education of a future citizen of Russia with a stable civic position, on the anticipatory nature of the development by future lawyers in the legal clinic of university of professional and personal competencies in demand in the rule of law.